Preface to the volume 2 issue 1 of Indian-Pacific Journal of Accounting and Finance - Popoola, Oluwatoyin Muse Johnson (OMJP Alpha Publishing, 2018)
It is a pleasure and admiration to welcome you to the Volume 2 Issue 1 of Indian-Pacific Journal of Accounting and Finance. In this Issue 1, the emphasis is placed on forensic accounting, accounting, auditing and corporate governance. In the first paper captioned “Mitigating Corruption Using Forensic Accounting Investigation Techniques: The Watchdog Perspectives”, Mr. Naziru Suleiman (Department of Accounting, Abubakar Tafawa Balewa University Bauchi, Nigeria) and Dr. Aidi Ahmi (Tunku Puteri Intan Safinaz School of Accountancy, Universiti Utara Malaysia) adopt qualitative research methodology based on in-depth interviews with experts from two prominent anti-corruption agencies to examine the efficacy of the technique. Data collected were manually coded and analysed using thematic analysis. Through rigorous within the case and cross-case analyses of the 24 interviews conducted, two themes emerged as the findings to the study. Forensic accounting is considered an appropriate technique for adequately investigating public sector corruption and at the same is suitable for court purposes in the prosecution and conviction of corrupt officers. Finally, the study recognises the need to enhance the capacity of the investigators through training and retraining as well as through the provision of the latest equipment for fighting corruption.In the second paper with a title “Internal Audit Functions: An empirical study of Public and Private Sectors in Nigeria”, Mr. Abdulkadir Madawaki (Department of Accounting, Al-Qalam University Katsina, Nigeria), Dr. Aidi Ahmi (Tunku Puteri Intan Safinaz School of Accountancy, Universiti Utara Malaysia) and Dr. Halimah @ Nasibah Ahmad (Tunku Puteri Intan Safinaz School of Accountancy, Universiti Utara Malaysia) examine the similarities and differences between the public and private sectors internal audit functions in Nigeria. The features examined include the hierarchical position of the internal audit functions, outsourcing of internal audit activities, reporting relationship of the internal auditor, and the coordination between internal and external auditors. A survey of internal audit managers of both sectors was undertaken to establish their current practices. The results revealed that there are no much differences in the hierarchical positioning of the internal audit function in both sectors. A substantial difference was found in the reporting lines of internal auditors in both sectors. The results further showed that private sector outsources internal audit activities more than the public sector and a slight difference exists between the two sectors about the level of coordination between internal and external auditors. Finally, the result indicated that private sector experience a reduction in external audit fees compares to its counterpart in the public sector. In the third paper entitled “The moderating effect of working capital management on the relationship between working capital determinants and firm performance”, Dr. Ahmad Rizal Mazlan (School of Economics, Finance and Banking, Universiti Utara Malaysia) and Dr. Choong Yuen Leng (Othman Yeop Abdullah Graduate School of Business, Universiti Utara Malaysia) examine working capital management moderating role on the relationship between the critical determinants of working capital and firm performance among 282 public-listed manufacturing firms in Malaysia for the period of 2010 to 2014. In this study, working capital management components are categorized into working capital requirement and net liquid balance. The evidence suggests that the relationship between critical determinants of working capital and firm performance is moderated by both working capital requirement and net liquid balance. Further, the results show that the research framework does form a contemporary working capital management model.In the fourth paper captioned “Firm Performance, Ownership Structure, and CEO Selection: The Case of Nigeria”, Yahya Uthman Abdullahi (Tunku Puteri Intan Safinaz School of Accountancy, Universiti Utara Malaysia), Dr. Rokiah Ishak (Tunku Puteri Intan Safinaz School of Accountancy, Universiti Utara Malaysia), and Dr. Norfaiezah Sawandi (Tunku Puteri Intan Safinaz School of Accountancy, Universiti Utara Malaysia) examine the effect of ownership structures, corporate performance and board political connectedness on CEO selection. The sample of the study is all Nigerian non-financial firms from the year 2011 to 2015, and consisting of 72 CEO selection events. This study uses logistic regression analysis to provide evidence that firms dominated with blockholder ownership favour external successors while managerial ownership-controlled firms are inclined to select internal candidates as successors. However, this study fails to support the argument that corporate performance and board political connectedness do influence the choice of CEO selection in the Nigerian public listed companies. In sum, the findings suggest that blockholders and managerial ownership significantly influence the choice of the origin of the successor CEOs in the Nigerian corporate landscape. This paper enriches the literature about CEO selection choices in developing economies with weak corporate governance structure like Nigeria. In addition, the findings from this study could be of immense benefit to the shareholders and corporate board members in deciding on recruiting their CEOs; and the regulatory agencies in the formulation and enforcement of reforms that guarantee good corporate practices by the boards In the fifth paper with the title “The impact of Audit Committee, Firm Size, Profitability, and Leverage on Income Smoothing”, Dr. Veronica Indrawan (Tarumanagara University, Tanjung Duren Utara, Indonesia), Prof. Dr. Sukrisno Agoes (Tarumanagara University, Tanjung Duren Utara, Indonesia), Dr. Hisar Pangaribuan (Adventist University of Indonesia, Bandung, Indonesia), and Dr. Oluwatoyin Muse Johnson Popoola (Tunku Puteri Intan Safinaz School of Accountancy, Universiti Utara Malaysia) examine the impact of the audit committee, firm size, profitability, and leverage on income smoothing in manufacturing companies listed in Indonesia stock exchange for the period of 2013-2015. Regression statistics are employed to analyse the secondary source of data collected from the annual report of the companies. Measurement of income smoothing is proxied by discretionary accruals. The results reveal that the firm size has a direct positive influence on income smoothing in the listed manufacturing companies in Indonesia. In essence, the more significant a firm size, the more actively performed income smoothing practices. In contrast, profitability indicates an adverse effect on income smoothing in the listed manufacturing companies. The adverse effect indicates that the higher the profit generated, the lesser the income smoothing practices performed. Similarly, leverage posits an adverse effect on income smoothing in the manufacturing sector. This indicates the smaller the risk of companies debt, the more exceptional the practice of income smoothing occurs. The audit committee size similarly shows a negative influence on income smoothing in the listed manufacturing companies. This finding indicates the larger audit committee size, the smaller practice of income smoothing. This occurs because the audit committee oversight function on financial reporting is more efficiently performed. The result of this research shows the contribution to theory, practice, and method, especially in developing countries As you read through this Volume 2 Issue 1, the success of IPJAF depends on your active participation and those of your colleagues and friends through submission of high-quality articles within the journal scope for review and publication. I cherish your continuous support in our quest to make IPJAF the most authoritative journal on accounting and finance for the community of academic, professional, industry, society and government.